Other Environmental Treaties Relevant for Human Rights Protection - Michalovič, Matúš (Human Rights and Environmental Protection from a Central and Eastern European Perspective, 2026)
This chapter explores how a group of “classic” sectoral environmental treaties operate, in practice, as tools for protecting human rights, with a particular focus on Central and Eastern European (CEE) countries. It examines treaties on nuclear safety and radioactive waste (the Convention on Nuclear Safety and the Joint Convention), transboundary air pollution (CLRTAP), ozone layer protection (the Vienna Convention and the Montreal Protocol), hazardous waste (the Basel Convention), and biological diversity (the Ramsar Convention, CITES, the Bonn Convention and the CBD). Across these regimes, the chapter traces how obligations to prevent environmental harm, manage risks and regulate dangerous activities translate into protection of the rights to life, health, food, water and a healthy environment. The CEE perspective is used to show how states with a legacy of heavy industry, nuclear energy and rich biodiversity rely on these treaties to address long-standing environmental pressures while meeting their human rights commitments. The chapter argues that, although most of these agreements are not framed as human rights instruments, their implementation has become an important part of how states discharge their human rights obligations. At the same time, it highlights persistent weaknesses, including soft or unevenly enforced obligations and the continued exposure of vulnerable communities to environmental harm. The conclusion invites readers to critically assess the effectiveness of these treaty regimes and to consider how future practice could better integrate environmental and human rights protection.